Ergocalciferol improves endothelial vasodilatory and vasoconstrictor function in an in vivo model of mild uraemia. Issue 12 (17th December 2019) - Dreyer, Gavin; Kieswich, Julius; Harwood, Steven; Ahluwalia, Amrita; Yaqoob, Muhammad M.
Abstract: Endothelial dysfunction and vitamin D deficiency are prevalent in patients with cardiovascular disease (CVD) and chronic kidney disease (CKD). Both are risk factors for cardiovascular events in patients with CKD. No studies have investigated the effect of nutritional forms of vitamin D on endothelial function in earlier stages of CKD, when vascular endothelium may be more amenable to this therapy. We studied the effect of ergocalciferol in a pre-clinical model of mild uraemia. Male Wistar rats underwent either a 5/6th nephrectomy or sham surgery. Four weeks after the final stage of the surgery, these two groups were randomly allocated to placebo or an oral dose of 1000 iu of ergocalcfierol at day 7 and 2 pre sacrifice. Vascular responses to acetylcholine, Spermine NONOate and phenylephrine were determined in aortic rings. Blood pressure, calcium, phosphate and parathyroid hormone were measured in all groups. Ergocalciferol significantly improved the endothelium-dependent responses to acetylcholine and overcame the blunting of the contractile response to phenylephrine seen in uraemic animals. Ergocalciferol improved the contractile response to potassium chloride in uraemic, but not sham animals. All effects occurred independently of changes to calcium, phosphate, parathyroid hormone and systolic blood pressure. There were no differences in endothelium-independent relaxation to Spermine NONOate. In summary, in a model of mild uraemia, ergocalciferol improved vasodilator and vasoconstrictor tone independently of blood pressure and bone mineral parameters suggesting a direct effect of ergocalciferol on the endothelium.